Characteristics of Indonesian Wild honey and Cultivited Honey and Their Antibacterial Activity against Staphylococcus aureus and Escherichia coli - Lusiani Tjandra; Budhi Setyawan; Masfufatun masfufatun (Universitas Wijaya Kusuma Surabaya, 2022)
Indonesia's natural wealth is very abundant in the form of flora and fauna that can be developed as raw materials for medicine. Honey in Indonesia is very diverse from Sabang to Merauke. Different types of honey are influenced by regional origin, season at harvest, type of bee, type of plant source of nectar, way of life of bees (cultivated or wild), harvesting method and post-harvest handling. This study aims to determine the characteristics of forest bee honey and cultivated honey and to determine the potential of honey as an antibacterial in the treatment of infectious diseases caused by Staphylococcus aureus and Escherichia Coli bacteria. The materials used were Carisa honey samples from Wild honey [Wild Klanceng and Wild Cerana] and Cultivation [Cerana Cultivation], S. aureus and E. coli bacteria. The characteristic test method is in accordance with the Indonesian National Standard and the honey inhibition test against the growth of S. aureus and E. Coli bacteria using the diffusion method. The results showed that Wild Cerana (WC) and Wild Klanceng (WK) honey demonstrated higher water content, ash content, acidity and glucose from Cerana Cultivated (CC) honey. Carissa Honey (beside Cerana cultivated honey) had antibacterial activity against S. aureus and E. Coli at different concentrations. Wild Wild Honey has the highest antibacterial activity compared to other types of honey. Conclusion Indonesian wild honey showed weak antibacterial activity against Staphylococcus aureus. Meanwhile, honey that is cultivated does not have antibacterial activity.